The investigation of clinical and radiological findings of hepatic alveolar cyst hydatid disease - Koç, Mustafa (My University, 2018)
Aim: The aim of this study is to investigate the clinical and radiological findings of hepatic alveolar hydatid cyst diagnosed in our clinic.Material and Methods: Records of patient files with histological diagnosis of hepatic alveolar hydatid cyst between March 2013 and February 2018 were retrospectively reviewed. Fifteen cases were included in the study. Nine of the cases were males (60 %) and 6 were females (40 %). Their ages ranged from 27 to 62 with a mean age of 41 ± 7.3 years. Clinical and laboratory findings and radiological imaging findings of the cases were investigated and recorded.Results: The most common symptoms were right upper quadrant pain (75 %), jaundice (24 %), fever (13 %) and weight loss (12 %). The most common finding in physical examinations was hepatomegaly (96 %). AST, ALT, and ALP values increased 3-4 times. Bilirubin values were generally increased (0.8-21.2 mg/dL). Abdominal ultrasonography (US) was described as a mass lesion with irregularly border, heterogeneous echogenicity, which consisted of the most solid component. It was located in the right liver lobe (82 %). Multislice Computed Tomography (MSCT) and Magnetic Resonance Imaging (MRI) findings supported the US findings. There was no contrast material involvement in the lesion. Diffusion MRI showed mild diffusion restriction somewhere.Conclusions: Alveolar echinococcosis frequently confused with other malignant liver lesions. Early diagnosis of the disease is very important in terms of treatment. Immunologic tests and biopsy are helpful in diagnosis. Radiological findings have an important role and contribution in the diagnosis of the disease.
Keywords: Genel ve Dahili Tıp; Patoloji; Onkoloji